Electrical resistivity and thermopower of Y1-xPrxCo2 Compounds. (18th March 2015) - Uchima, K; Teruya, A; Takaesu, Y; Akamine, H; Kakihana, M; Tomori, K; Uejo, T; Nakamura, A; Hedo, M; Nakama, T; Yagasaki, K; Burkov, A T
Abstract: Electrical resistivity ρ and thermopower S of the pseudo-binary compounds of Y1- x Pr x Co2 have been measured in the temperature range between 2 and 300 K under magnetic fields up to 10 T, together with the pressure measurements of ρ and S in Y0.4 Pr0.6 Co2 . The Curie temperature decreases with decreasing x, and vanishes at the critical composition xc ≈ 0.4, where the residual resistivity attains a maximum value. The Curie temperature and the residual resistivity of Y0.4 Pr0.6 Co2 show the same pressure dependence as those of the heavy-rare-earth based compounds. These behaviors of ρ and S indicate the inhomogeneous distribution of the Co 3d magnetization. The magnetoresistance of the light-rare earth Y1- x Pr x Co2 system is negative in the whole range of x, except for x = 0 and 1, which is a characteristic behavior related with magnetic state and magnitude of the effective field acting on the Co 3d subsystem.